2017
DOI: 10.14301/llcs.v8i2.415
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal methods for life course research: A comparison of sequence analysis, latent class growth models, and multi-state event history models for studying partnership transitions

Abstract: CPC centre for population changeImproving our understanding of the key drivers and implications of population change Longitudinal methods for life course research: A comparison of sequence analysis, latent class growth models, and multistate event history models for studying partnership transitions ABSTRACT This paper compares and contrasts three methods that are useful for life course researchers; the more widely used sequence analysis, the promising but less often applied latent class growth models, and mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 20 publications
1
19
0
1
Order By: Relevance
“…It is opposed to conventional approaches in epidemiology that consider each state independently from one another. The comparison of SSA with other methods, which can be appropriate for the study of a care pathway, such as latent class analysis (LCA), revealed that both methodologies yield similar clustering results 41,49,50 . These studies have highlighted that SSA is easier to use and to compute than LCA and that, unlike LCA, it does not require specification of a model.…”
Section: Table 4 Here 4 Discussionmentioning
confidence: 99%
“…It is opposed to conventional approaches in epidemiology that consider each state independently from one another. The comparison of SSA with other methods, which can be appropriate for the study of a care pathway, such as latent class analysis (LCA), revealed that both methodologies yield similar clustering results 41,49,50 . These studies have highlighted that SSA is easier to use and to compute than LCA and that, unlike LCA, it does not require specification of a model.…”
Section: Table 4 Here 4 Discussionmentioning
confidence: 99%
“…A weekly labour state measure could have led to underestimation of short employment spells because approximately one-fth of these were less than four days (results not shown). Another limitation comes from the use of two modelling methods based on simplifying assumptions, which may have implications for the robustness and reliability of the results; therefore, any conclusion derived should be considered carefully [17,52]. In this regard, LMP patterns in the early working life cohorts may not represent homogeneous groups because their global ASW showed lower values than recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a certain cost is attached to each operation. The distance between two sequences is defined by the minimum cost of the operations (replacement, insertion, or deletion) that is required for two sequences to become identical (Abbott 1995;Abbott and Tsay 2000;Barban and Billari 2012;Billari 2001b;Mikolai and Lyons-Amos 2017). The distances are stored in a dissimilarity matrix.…”
Section: Methodsmentioning
confidence: 99%
“…We included a number of independent variables in the multinomial logistic regression to understand how individual characteristics predict cluster membership of separated individuals. It is not possible to include time-varying covariates in sequence analysis (Mikolai and Lyons-Amos 2017); therefore, all covariates were measured at the time of separation. Educational level was measured as low (O level, CSE, none), medium (A level), and high (university degree or teaching qualification).…”
Section: Variablesmentioning
confidence: 99%